PENERAPAN METODE ITERATIVE DICHOTOMIZER (ID3) UNTUK DIAGNOSA HAMA TANAMAN ANGGREK - Fathul Hafidh; Muhammad Edya Rosadi; Rahmadi Agus (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2017)
Orchid plants is one component of the aesthetic aspect and become a part of human life. Diagnostics system for classification orchid pests were attack plants still using the manual model, it’s result difficulty identifying pests orchid that has a variety of symptoms are almost the same. As to distinguish the symptoms of damage to the leaves, roots and flowers caused by pests. ID3 able to generate a decision tree of large data sets. This decision tree can be used as a reference for the diagnosis of pests on orchids. In this research, pest classification of orchids do with ID3 method with the highest level of performance accuracy is 78.06%.